Use of a portable field-adapted liquid chromatographic system (C-Vue machine) to estimate the quantity of deltamethrin on insecticide-treated nets paired with WHO cone bioassays to determine ITN bioefficacy as part of three-year durability monitoring in Mali - Moussa B. M. Cisse; Ibrahim Traore; Mamadou Sow; Yacouba Dansoko; Alice Dembele; Lazeni Konate; Jean-Marie Sanou; Youssouf Diarra; Samah Sissoko; Abdourhamane Dicko; Mahamadou Magassa; Lansana Sangare; et al. (Malaria Journal)
Abstract Background Monitoring insecticide levels and physical integrity over time is essential for assessing the durability of insecticide-treated nets (ITNs), which largely depends on the net handling habits of users. This study determined the insecticide content and effectiveness of ITNs (Yorkool and PermaNet 2.0) at 6, 12, 24, and 36 months after a mass distribution campaign in Mali. Methods At 6 months (May, 2018), 12 months (December, 2018), 24 months (November–December, 2019), and 36 months (November–December, 2020), 30 nets were randomly collected from households in the districts of Kenieba and Kita in the southern part of Mali, together with information about ITN use and washing practices. The insecticidal effectiveness of the ITNs was assessed with the World Health Organization (WHO) cone test using a laboratory-reared, susceptible colony of Anopheles coluzzii. The residual insecticide content was measured by a nondestructive sampling technique with a portable field-adapted high-performance liquid chromatographic (HPLC) system (C-Vue®) validated by running samples in parallel with standardized WHO HPLC methods. Results At each survey time, nets were washed an average of three times over the previous 6 months, most commonly using Local soaps containing sodium hydroxide, detergent, or bleach. Using HPLC_CVue, the average deltamethrin concentration was 55 mg/m2 at 6 months and gradually decreased to 14 mg/m2 at 36 months for Yorkool nets. The values for the PermaNet 2.0 nets were 45 mg/m2 at 6 months and 6 mg/m2 at 36 months. Until the 24-month evaluation, the proportion of nets with minimal effectiveness was greater than 80% for both net types and sites. At 24 and 36 months, less than 80% of nets from both products and sites met the WHO optimal effectiveness criteria. Conclusion The WHO standardized cone test and C-Vue evaluation demonstrated that net type effectiveness and insecticide content were consistently lower than expected at 3 years, and users washed nets with local soaps containing sodium hydroxide, detergent or bleach. The C-Vue portable chromatographic device was used successfully for the first time in Mali to measure the insecticide concentration of ITNs.